2012
DOI: 10.1371/journal.pone.0053502
|View full text |Cite
|
Sign up to set email alerts
|

A New Test of Attention in Listening (TAIL) Predicts Auditory Performance

Abstract: Attention modulates auditory perception, but there are currently no simple tests that specifically quantify this modulation. To fill the gap, we developed a new, easy-to-use test of attention in listening (TAIL) based on reaction time. On each trial, two clearly audible tones were presented sequentially, either at the same or different ears. The frequency of the tones was also either the same or different (by at least two critical bands). When the task required same/different frequency judgments, presentation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 45 publications
2
40
0
1
Order By: Relevance
“…This suggests that sustained auditory attention skills can contribute to fine acoustic perception (further to Ahissar et al, 2009) -but that these attentional skills are modality-delimited, as shown by the lack of relationship between the SAART measures and visual psychophysics performance (see Braga et al, 2013, for a recent demonstration of the modality-specific nature of attentional systems). Our PCA analyses also found that auditory psychophysical performance loaded with sustained auditory attention performance on a single component, thereby further supporting a relationship between auditory attention and some fine perceptual abilities in both musicians and non-musicians (Strait et al, 2010(Strait et al, , 2012bStrait & Kraus, 2011b;Tervaniemi et al, 2005; see also Zhang et al, 2012).…”
Section: Sustained Attention and Perceptual Performancesupporting
confidence: 73%
See 1 more Smart Citation
“…This suggests that sustained auditory attention skills can contribute to fine acoustic perception (further to Ahissar et al, 2009) -but that these attentional skills are modality-delimited, as shown by the lack of relationship between the SAART measures and visual psychophysics performance (see Braga et al, 2013, for a recent demonstration of the modality-specific nature of attentional systems). Our PCA analyses also found that auditory psychophysical performance loaded with sustained auditory attention performance on a single component, thereby further supporting a relationship between auditory attention and some fine perceptual abilities in both musicians and non-musicians (Strait et al, 2010(Strait et al, , 2012bStrait & Kraus, 2011b;Tervaniemi et al, 2005; see also Zhang et al, 2012).…”
Section: Sustained Attention and Perceptual Performancesupporting
confidence: 73%
“…These results conform to research with other highly skilled populations such as chess players, birders, and memory experts, showing that experts differ from non-experts in both their GENERALITY AND SPECIFICITY IN MUSICAL EXPERTISE EFFECTS 10 attention to key stimulus features, and their ability to sustain such attention over extended periods (see Palmeri et al, 2004;Green & Bavelier, 2012). Such potential differences in attentional abilities are not only interesting in their own right, but are particularly important in understanding what might drive musicians' advantages in lower-level auditory perception (see Kraus, 2011b, andZhang et al, 2012, for discussion). For instance, attention is known to modulate auditory detection (e.g., via attentional cuing to specific frequency bands; Mondor & Bregman, 1994; Justus & List, 2005;Larkin & Greenberg, 1970;Greenberg & Larkin, 1968), and attention can interact with the saliency of acoustic cues in auditory search tasks (Kayser et al, 2005).…”
Section: Auditory Attention and Influence On Perceptionmentioning
confidence: 99%
“…Other authors have attributed high within-participant variability obtained on a frequency discrimination task to fluctuations in attentional allocation and control (Moore et al, 2008;Moore et al, 2010). In one study of normal adult listeners, 45% of the variance in performance on a frequency discrimination task was accounted for by attentional variables (Zhang et al, 2012). Our meta-regressions were not able to fully test the impact of attentional variables on FD because most of the included studies did not contain relevant measures of attention.…”
Section: Task Design and Other Moderator Variablesmentioning
confidence: 87%
“…Dyslexia also has high levels of diagnostic co-occurrence with attention-deficit hyperactivity disorder (ADHD), where from 25 to 40% of children with either dyslexia or ADHD meet the diagnostic criteria for the other (Wilcutt & Pennington, 2000). Because some attention skills also co-vary with psychophysical task performance, both in children (Moore, Ferguson, Edmondson-Jones, Ratib, & Riley, 2010;Moore, Ferguson, Halliday, & Riley, 2008;Talcott, Witton, & Stein, 2013), adults (Zhang, Barry, Moore, & Amitay, 2012), and in simulations of non-expert listeners (Witton et al, 2017), it is likely that the frequency discrimination impairments reported in the literature were also influenced to some degree by factors other than the reading skills that primarily distinguish the dyslexic listeners from the control groups. Despite this, few studies of frequency discrimination in dyslexia have sufficiently measured attention skills, or consistently screened for ADHD symptoms, in their participants.…”
Section: Potential Sources Of Heterogeneity In Auditory Processing mentioning
confidence: 99%
“…In another study, behavioral tests designed to tax top-down auditory attention were able to account for some of the variability in listening performance in complex settings for normal-hearing adult listeners (e.g., Zhang et al, 2012). These types of results suggest that cognitive factors such as the ability to consciously direct attention to stimuli (or tasks) of interest play an important role in hearing in complex settings.…”
Section: Potential Applications For (C)apd (And Beyond)mentioning
confidence: 99%